2018
DOI: 10.1002/jcb.28241
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Deep integrative analysis of microRNA‐mRNA regulatory networks for biomarker and target discovery in chondrosarcoma

Abstract: Chondrosarcoma (CHS) is a common malignant bone sarcoma and its occurrence increases with age. microRNAs (miRNAs) are a class of noncoding RNAs that participate in various biological processes and disease pathogenesis by targeting functional messenger RNA (mRNA). However, the modulation of miRNAs in CHS remains largely unknown. In this study, we performed integrative analysis to explore the expression profiles of miRNAs and mRNAs, together with their interaction networks in human CHS tissues and cell lines by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…(37)(38)(39) Reduced levels of miR-143 or miR-145 have been reported in other tumor entities, and both molecules are generally acknowledged as tumor suppressors. (40,41) Our results are consistent with a recent publication showing miR-145 downregulation in chondrosarcoma (42) , however, the authors analyzed only a small cohort of five clinical samples without investigating miRNA functionality. Importantly, and in contrast to previous reports, our results are strengthened by an analysis of a considerably larger (42 samples) cohort.…”
Section: Discussionsupporting
confidence: 91%
“…(37)(38)(39) Reduced levels of miR-143 or miR-145 have been reported in other tumor entities, and both molecules are generally acknowledged as tumor suppressors. (40,41) Our results are consistent with a recent publication showing miR-145 downregulation in chondrosarcoma (42) , however, the authors analyzed only a small cohort of five clinical samples without investigating miRNA functionality. Importantly, and in contrast to previous reports, our results are strengthened by an analysis of a considerably larger (42 samples) cohort.…”
Section: Discussionsupporting
confidence: 91%
“…While we cannot find any relevant data regarding miR-6132 and tumors, the expression of miR-22 and miR-4539 in cancer tissue has been studied in gastric cancer, rhabdomyosarcoma, breast cancer, prostate cancer, osteosarcoma and papillary thyroid cancer (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Most studies have reported that, in contrast to their expression levels in the blood, the expression levels of these miRNAs are decreased in cancer tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Another study found out candidate miRNA-mRNA network that could be utilized to predict chemoresistance response in osteosarcoma (13). Moreover, a study provided a meaningful characterization of miRNA-mRNA co-expression network in chondrosarcoma and identified crucial miRNAs and mRNAs involved in chondrosarcoma carcinogenesis (14).…”
Section: Introductionmentioning
confidence: 99%